TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENCURIAN DI MASA PANDEMI COVID-19 DI KECAMATAN PANAKKUKANG KOTA MAKASSAR: JURIDICAL REVIEW OF THE CRIMINAL ACTION OF THEY IN THE COVID-19 PANDEMIC TIME IN PANAKKUKANG DISTRICT, MAKASSAR CITY - Hidayat, Dita Hardianti; Yamin, Muhammad Halwan; Fadly (Clavia, 2020)
This study aims to determine the responsibility of the perpetrators of theft during the Covid-19 pandemic and to determine whether theft during the pandemic is an element of weighting against the perpetrators of criminal acts. The research method used is an empirical research method, namely by using literature study techniques, documents, and interviews with respondents. The research results show that (1) Based on the legal facts regarding the series of actions of each suspect, the suspects can be held accountable for their actions as the article alleged against the suspects, namely article 362 paragraph (2) of the Criminal Code because the series of actions of the suspects fulfilled all elements in article 362 paragraph (2) of the Criminal Code. (2) In cases of theft during the Covid-19 pandemic that occurred at Agustina Tanda's residence on Jalan H. Kalla II No. 8 Makassar City, in the legal area of the Panakukang Police, did not find any weighting of criminal responsibility to the suspects due to the theft situation during the Covid-19 Pandemic but because in the series of actions of the suspects there were burdensome elements so that the series of actions of the suspects no longer only fulfilled the elements of the article of theft Ordinary, namely 362 KUHPidana with a maximum penalty of 5 (five) years but also fulfills the elements of the article of theft with a weighting as regulated in Article 363 paragraph (2) of the Criminal Code with a maximum penalty of 9 (nine) years.